Χάραξη οδηγού καμπύλης και λειτουργία ΥΗΕ Ιλαρίωνα (ΔΕΗ) - Σπανομανώλης Ιάσων (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Ρευστών, 2014)
The optimization of a hydrosource is a complex subject. In order for the optimization to be achieved, a lot of derivatives have to be taken into account, with many having conflicting aspects.In most cases this optimization is not involved just with the maximization of the energy produced and the energy performance coefficient, but has many other aspects, such as the withholding of volumes of water for less affluent periods, the technical boundries of the development, the seasonal needs of the overall network, the ecological behavior of the plant and more.The main reason that leads to the saidcomplexity is the stochastic nature of the imput data, which is the incoming flow of the river. The operating model should guarantee safe and acceptable operation in a variety of circumstances, from severe draughts to tidal situations.This diploma thesis is involved withthe creation of the Target Head Curve and the Operating Model for the Hilarion Hydroelectric Plant built bythe Public Power Corporation of Greece.